CREATIVE LEADERSHIP OF SCHOOL ADMINISTRATORS THAT AFFECT THE EFFECTIVENESS OF SCHOOLS UNDER NAKHON SRI THAMMARAT PRIMARY EDUCATIONAL SURVICE AREA OFFICE 1 - Nurak, Natchanon; Klinmalee, Rattaporn; Chatakan, Werayut (Journal of MCU Nakhondhat, 2023)
The research of the Creative Leadership of school administrators that affect the effectiveness of schools under Nakhon Sri Thammarat Primary Educational Service Area Office 1 research aimed to firstly, study Creative Leadership of schools under Nakhon Si Thammarat Primary Educational Service Area Office 1 secondly, study the effectiveness of schools under Nakhon Sri Thammarat Primary Educational Service Area Office thirdly, study Creative Leadership of school administrators that affect the effectiveness of schools under Nakhon Sri Thammarat Primary Educational Service Area Office and finally ,study Guidelines development of Creative Leadership of schools under Nakhon Sri Thammarat Primary Educational Service Area Office 1 Research subjects were 306 teachers. The research findings were as follow 1) The overall creative leadership were having a high score. 2) the overall score of the effectiveness of schools were having a high score. 3)Creative Leadership of school administrators that affect the effectiveness of schools under Nakhon Sri Thammarat Primary Educational Service Area Office 1 found that all factors of Creative Leadership which is consisted of vision, creativities, Imagination and Flexibility gave a positive sign to the school. The overall score has highly related (r=.81**) 4) Solution of Guidelines development of Creative Leadership of schools under Nakhon Sri Thammarat Primary Educational Service Area Office 1 Vision: the board of director should look for a long term strategy, always looking for an opportunity to improve the school Creativities: board of director should look for more innovation in order to develop school Imagination; board of director should have good logic , optimistic and a good communicator Flexibility: board of director should adapt himself/herself to the surrounding people the environment